Pengaruh Kepemilikan Institusional, Dewan Komisaris Independen, Dewan Direksi Dan Komite Audit Terhadap Kinerja Keuangan Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2021-2024 - Putu Eni Ulantari; Ni Putu Ayu Kusumawati; Ni Ketut Muliati (Hita Akuntansi dan Keuangan, 2026)
The financial industry has become a battleground of intensifying competition, fueled by the sweeping tide of digitalization and rapid technological progress over the past decades. This transformation has not only altered business practices but also reshaped how individuals engage with financial services. The emergence of fintech, bigtech, and digital banking has added new layers of rivalry, pushing firms to innovate and adapt. Digital adoption is seen as a pathway to greater efficiency, improved effectiveness, and enhanced convenience in both transactions and customer interactions. Against this backdrop, the present study explores the role of institutional ownership, independent boards of commissioners, boards of directors, and audit committees in shaping financial performance. Using secondary data from 136 companies’ annual reports, the research applies multiple linear regression to analyze the relationships. Results demonstrate that institutional ownership, independent commissioners, and boards of directors significantly strengthen financial performance, while audit committees do not exhibit a meaningful influence